Treosulfan in the treatment of advanced ovarian cancer: results of a German multicenter non-interventional study - Chekerov, Radoslav; Wischnik, Arthur (Anticancer research, 2015)
Background: Data on routine systemic treatment of patients with ovarian cancer are currently available only to a limited degree. The alkylating agent treosulfan is approved in oral (p.o.) and intravenous (i.v.) form for the treatment of ovarian carcinoma. The present non-interventional study analyzed the clinical use of treosulfan in Germany, evaluating the mode of application, toxicity, and response and survival rate. Patients and Methods: Two hundred and forty-eight ovarian cancer patients in 57 Centers, who received treosulfan mainly either i.v. (5,000-8,000 mg/m2 d1, q21d or q28d) or p.o. (400-600 mg/m2 d1-14 or 21, q28d) for at least one therapy cycle were evaluable and were included in the study. Results: With a median age of 70 years (range=36-92 years), predominantly elderly patients received treosulfan treatment. Most participants presented serous histology (131, 52.8%) and advanced-stage FIGO III (122, 49%) or IV (55, 22%) disease. Median ECOG status was 1 (range=0-2), whereas cardiac co-morbidity was common (31%). Treosulfan was usually administered as second- (26%), third- (21%) or fourth-line (17%) therapy. Two hundred and one patients received i.v. and 47 p.o. treatment. The most common reason for dose modifications was due to hematological toxicity (46%). The main reason for a therapy discontinuation was progressive disease (38.5%). Response was observed in 25.8% of participants, disease stabilization in 28.6 % and progress in 45.6%. The median progression-free and overall survival was 196 and 405 days, respectively. Conclusion: In predominantly elderly and heavily pre-treated patients with recurrent ovarian cancer, treosulfan featured a clinical relevant efficacy and well-manageable, mostly hematological, toxicity, which resulted in a positive therapeutic index.
Gesehen am 29.11.2018